Crystallization Properties of Mg35Sb65/Sb Nanocomposite Multilayer Films for Phase Change Memory Application. (1st January 2019) - Sun, Song; Hu, Yifeng; Xu, Yongkang; Lai, Tianshu; Zhu, Xiaoqin
Abstract : The phase transition properties of Mg35 Sb65 /Sb multilayer thin films were studied, including the crystallization mechanism, surface morphology, atomic bonding mode and adhesion strength. With the increase of the thickness of Mg35 Sb65 interlayers, Mg35 Sb65 /Sb thin film had better thermal stability and lower electrical conductivity. The growth-dominated crystallization mechanism made Mg35 Sb65 /Sb have ultra-fast phase change speed. The subtle change on surface morphology was ascribed to the grain growth and interface stress during crystallization. The scratch test revealed the adhesion strength contrast before and after crystallization. This work showed that Mg35 Sb65 /Sb multilayer film was a potential material with fast speed and good thermal stability for phase change memory application.